Symbolic Violence Toward the Main Character Bianca Pieper in The Script of The Movie The Duff (2015) - Desi Priskawati; Ferra Dian Andanty (Universitas Pendidikan Indonesia, 2023)
This study aims to describe the symbolic violence experienced by Bianca Pieper and Bianca Pieper's response to symbolic violence. Symbolic violence is invisible violence because it is not physical violence. Symbolic violence is carried out by a person or group that dominates another class and results in a violent process. The problem is that Bianca Pieper, the main character in The Duff, experiences symbolic violence and how she responds to this symbolic violence. The method used to collect data is a movie script. Data analysis techniques carried out descriptively, then followed by conclusion. In conclusion, it shows that Bianca Pieper received symbolic violence from the people around her, such as her friends. In addition, the writer knows how Bianca reacted to the symbolic violence she experienced.